Analysis of Opportunities and Challenges Of Sustainable Financing For Micro, Small, And Medium Enterprises - Agustina, Amalia; Alwiyanti, Meilani (Terbuka Journal of Economics and Business, 2024)
Sustainable financing has become a key focus in financing an inclusive and sustainable economy. MSMEs have a role to play in the global economy to cultivate the sustainability of MSMEs in Indonesia. However, MSMEs often face challenges in accessing financing necessary for their growth and sustainability. This paper discusses the literature related to sustainable financing for MSMEs. The purpose of this paper is to analyze the opportunities and challenges of sustainable financing for MSMEs. Using the literature review method, this paper also explores the basic concepts of sustainable financing as well as the principles related to the analysis of opportunities and challenges of sustainable financing for MSMEs. In addition, this paper also explores a number of challenges faced by MSMEs in implementing sustainable financing, such as limited access to financing sources and risks associated with MSME financing in Indonesia. Through an in-depth review of available literature and data, this research provides a better knowledge of the facts that need to be considered to increase MSMEs' awareness of sustainable financing. The conclusion of this literature review is that the Analysis of Opportunities and Challenges of Sustainable Financing for MSMEs has great potential to support economic growth and sustainability of MSMEs, for this reason MSMEs need to have an awareness of capturing innovation opportunities, be creative in marketing products that will be cultivated in a competitive society by seeking information on sustainable financing for MSMEs and preparing themselves for the challenges of implementing sustainable financing.